Clinical Features of End Stage Renal Disease yang Menjalani Hemodialisis di RS Tk.II dr. Soedjono Magelang - Endro Haksara; Ainnur Rahmanti; Margiyati Margiyati; Indah Septiyani Triabadi (Lembaga Pengembangan Kinerja Dosen, 2024)
Clinical Features of End Stage Renal Disease (ESRD) will appear if urea blood levels is more than 200 mg/dl. Uremia can cause malfunctioning of all organ systems, such as; disorder of fluid and electrolyte balance, endocrine- metabolic, neuromuscular, cardiovascular and lung, skin, gastrointestinal, hematology and immunology systems. The objective of this study was to determine the clinical features of patients with ESRD that undergoing hemodialysis at RS Tk.II dr. Soedjono Magelang. This was a descriptive observational method based on secondary data obtained from medical records. Samples included all patients with ESRD underwent hemodialysis at RS Tk.II dr. Soedjono Magelang in 2023 who were fulfilled inclusion criteria, with total 104 samples. Data were analyzed by using univariate analysis. The study showed that patients with ESRD were mostly at ranged 40 to 60 years (62.5%) and predominantly men (59 patients, 56.7%). The most clinical features of the patient were moderate nutritional status (94.2%), with Hb concentration 7-10g/dl (68.3%), conjunctival anemia (62.5%), peripheral edema (53.8%), stage 1 hypertension (32.7%), weakness and tired (30.8%), and nausea (12,7%). The conclusion is the most common clinical features of the patients with ESRD undergoing hemodialysis at RS Tk.II dr. Soedjono Magelang were anemia, with first stage hypertension, moderate nutritional status and peripheral edema.